Neuroprotective Mechanism of Lycium barbarum Polysaccharides against Hippocampal-Dependent Spatial Memory Deficits in a Rat Model of Obstructive Sleep Apnea - Lam, Chun-Sing (PLoS One, 2015)
Chronic intermittent hypoxia (CIH) is a hallmark of obstructive sleep apnea (OSA), which induces hippocampal injuries mediated by oxidative stress. This study aims to examine the neuroprotective mechanism of Lycium barbarum polysaccharides (LBP) against CIH-induced spatial memory deficits. Adult Sprague–Dawley rats were exposed to hypoxic treatment resembling a severe OSA condition for a week. The animals were orally fed with LBP solution (1mg/kg) daily 2 hours prior to hypoxia or in air for the control. The effect of LBP on the spatial memory and levels of oxidative stress, inflammation, endoplasmic reticulum (ER) stress, apoptosis and neurogenesis in the hippocampus was examined. There was a significant deficit in the spatial memory and an elevated level of malondialdehyde with a decreased expression of antioxidant enzymes (SOD, GPx-1) in the hypoxic group when compared with the normoxic control. In addition, redox-sensitive nuclear factor kappa B (NFКB) canonical pathway was activated with a translocation of NFКB members (p65, p50) and increased expression levels of NFКB-dependent inflammatory cytokines and mediator (TNFα, IL-1β, COX-2); also, a significantly elevated level of ER stress (GRP78/Bip, PERK, CHOP) and autophagic flux in the hypoxic group, leading to neuronal apoptosis in hippocampal subfields (DG, CA1, CA3). Remarkably, LBP administration normalized the elevated level of oxidative stress, neuroinflammation, ER stress, autophagic flux and apoptosis induced by hypoxia. Moreover, LBP significantly mitigated both the caspase-dependent intrinsic (Bax, Bcl2, cytochrome C, cleaved caspase-3) and extrinsic (FADD, cleaved caspase-8, Bid) signaling apoptotic cascades. Furthermore, LBP administration prevented the spatial memory deficit and enhanced the hippocampal neurogenesis induced by hypoxia. Our results suggest that LBP is neuroprotective against CIH-induced hippocampal-dependent spatial memory deficits by promoting hippocampal neurogenesis and negatively modulating the apoptotic signaling cascades activated by oxidative stress and inflammation.